2017
DOI: 10.3892/etm.2017.4663
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase A1 mediates nicotine-induced lung cancer cell metastasis by promoting epithelial-mesenchymal transition

Abstract: Abstract. The present study aimed to investigate the effect of glutathione S-transferase A1 (GSTA1) on lung cancer cell viability, invasion and adhesion in the presence of nicotine in vitro. Furthermore, the effect of GSTA1 on the epithelial-mesenchymal transition (EMT), a process strongly associated with lung cancer metastasis, was examined. Human lung carcinoma A549 cells were treated with various concentrations of nicotine (0.01, 0.1, 1 and 10 µM) and levels of GSTA1 mRNA and protein were measured by revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Moreover, both genes are local hubs of mAEC network while GSTM3 is also a bottleneck, thus suggesting a driving role in the induction of EMT. In agreements with these results, GSTA1-1 and GSTM3 have been recognized as stimulatory respect proliferation, apoptosis evasion, metastatic process and EMT-related genes induction [52][53][54] .…”
Section: Klhl14supporting
confidence: 56%
“…Moreover, both genes are local hubs of mAEC network while GSTM3 is also a bottleneck, thus suggesting a driving role in the induction of EMT. In agreements with these results, GSTA1-1 and GSTM3 have been recognized as stimulatory respect proliferation, apoptosis evasion, metastatic process and EMT-related genes induction [52][53][54] .…”
Section: Klhl14supporting
confidence: 56%
“…Eight isoforms of cytosolic-soluble GSTs have been recognized in humans, including α, κ, μ, π, σ, θ, ζ, and ω 3,4 . Glutathione S-transferase α1 (GSTA1, Gene ID: 2938) has shown both stimulatory [5][6][7][8] and inhibitory effects [9][10][11][12] on tumorigenesis. The association between genetic polymorphism of GSTA1 and susceptibility to cancer has been discussed in previous studies [13][14][15] , but…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Dasgupta P et al [18] showed nicotine, an active component of cigarettes, had been found to cause down-regulation of E-cadherin and up-regulation of Vimentin in lung cancer cell line A549 in vitro. The aged, smoking male tend to suffer lung squamous carcinoma from the standpoint of clinical medicine.…”
Section: Grading Journal Of Biosciences and Medicinesmentioning
confidence: 99%